Signs and Symptoms of Dry Eye in Keratoconus Patients Before and After Intrastromal Corneal Rings Surgery. (3rd April 2017) - Carracedo, Gonzalo; Recchioni, Alberto; Alejandre-Alba, Nicolás; Martin-Gil, Alba; Batres, Laura; Morote, Ignacio Jimenez-Alfaro; Pintor, Jesús
ABSTRACT: Purpose : Based on the relationship between keratoconus and dry eye, the aim of this study was to evaluate changes in signs and symptoms of dry eye in keratoconus patients before and after intrastromal corneal ring surgery. Methods : Fifteen keratoconus patients were enrolled in Fundación Jiménez-Díaz of Madrid and University Clinic of Optometry of the Universidad Complutense de Madrid (Madrid, Spain). Tear break up time (TBUT), Schirmer test without anesthesia, corneal staining, diadenosine tetraphosphate (Ap4 A) concentration, and ocular surface disease index (OSDI) were evaluated. Impression cytology combined with laser confocal microscopy was performed to evaluate goblet cell density, mucin cloud height (MCH), and cell layer thickness (CLT). All measurements were performed before (pre) surgery, 1 month (post) and 6 months after surgery (post6m). Results : We found no statistical differences in time in Schirmer test, TBUT, and corneal staining. OSDI scores were 44.96 ± 8.65, 26.30 ± 6.79, and 19.31 ± 4.28 for (pre), (post), and (post6m) surgery, respectively ( p < 0.001). Impression cytology showed a decrease in cell density at (post6m) compared with presurgery (47.36 ± 35.15 cells/mm 2 and 84.88 ± 32.08 cells/mm 2, respectively, p = 0.04). At post6m, the MCH increased compared with presurgery values (13.97 ± 4.26 µm and 6.77 ± 2.51 µm, respectively, p < 0.001). There was a statistically significant increase in CLT in time. Ap4 A tear concentrations were lower post6m than presurgery (1.02 ± 0.65 and 2.56 ± 1.10 µM, respectively, p < 0.001). Conclusion :I ntrastromal corneal ring surgery induces changes improving dry eye symptoms but no changes were found in signs of dry eye after surgery in keratoconus patients except for the MCH that increases drastically. More studies are needed to clarify the reason of its improvement.